2014
DOI: 10.1371/journal.pone.0093694
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Magnetic Resonance Imaging as an Accurate and Reliable Tool to Diagnose and Monitor Esophageal Cancer in a Rat Model

Abstract: ObjectiveTo assess the reliability of magnetic resonance imaging (MRI) for detection of esophageal cancer in the Levrat model of end-to-side esophagojejunostomy.BackgroundThe Levrat model has proven utility in terms of its ability to replicate Barrett’s carcinogenesis by inducing gastroduodenoesophageal reflux (GDER). Due to lack of data on the utility of non-invasive methods for detection of esophageal cancer, treatment efficacy studies have been limited, as adenocarcinoma histology has only been validated po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…For the first time, we demonstrated macro-metastatic lesions originating from the primary tumors in the model[ 30 ]. Additionally, we further enhanced the utility of the model through combined magnetic resonance imaging (MRI) and small animal endoscopic biopsy to simultaneously track in vivo tumor volumes and molecular correlates longitudinally[ 31 ]. With these advancements, the animal model has been highly efficient, not only to develop preventative and treatment strategies, but also to provide a platform to better understand the molecular mechanisms that affect disease progression from inflammation to EAC.…”
Section: Discussionmentioning
confidence: 99%
“…For the first time, we demonstrated macro-metastatic lesions originating from the primary tumors in the model[ 30 ]. Additionally, we further enhanced the utility of the model through combined magnetic resonance imaging (MRI) and small animal endoscopic biopsy to simultaneously track in vivo tumor volumes and molecular correlates longitudinally[ 31 ]. With these advancements, the animal model has been highly efficient, not only to develop preventative and treatment strategies, but also to provide a platform to better understand the molecular mechanisms that affect disease progression from inflammation to EAC.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to follow-up, endoscopic assessment is erratic due to extraluminal development of majority of tumors and low yield from endocopic biopsies in rats. Recently, Kosovec et al 41 demonstrated the usefulness and advocated the use of MRI rather than endoscopy for tumor assessment during follow-up. In conclusion, there is a need for a better model to overcome these concerns.…”
Section: Rat Modelsmentioning
confidence: 99%
“…Mice models are well-suited for molecular studies given that their genome is completely sequenced and transgenic mice are commercially available today. 42 There have been many attempts to utilize genetically modified [41][42][43][44][45][46] and xenograft mice models [47][48][49] in BE research. However, creation of reflux in mice models often leads to many dying in the early postoperative period due to difficulty in performing surgery at the scale of their sizes and their intolerance to surgical stress.…”
Section: Mice Modelsmentioning
confidence: 99%
“…Anastomosis reinforcement models focus on leaks and dehiscence and have been described at different anatomic locations in the esophagus in the dog. 138 The Levrat procedure is a well-established model involving an esophagojejunostomy, a procedure that produces retrograde flow of gastrointestinal contents into the distal part of the esophagus, resulting in Barrett's esophagus and eventually progressing to esophageal adenocarcinoma [139][140][141][142][143] (Fig. 7).…”
Section: Animal Models For Esophageal Repairmentioning
confidence: 99%